2018
DOI: 10.13001/1081-3810.3578
|View full text |Cite
|
Sign up to set email alerts
|

On the Largest Distance (Signless Laplacian) Eigenvalue of Non-transmission-regular Graphs

Abstract: Let $G=(V(G),E(G))$ be a $k$-connected graph with $n$ vertices and $m$ edges. Let $D(G)$ be the distance matrix of $G$. Suppose $\lambda_1(D)\geq \cdots \geq \lambda_n(D)$ are the $D$-eigenvalues of $G$. The transmission of $v_i \in V(G)$, denoted by $Tr_G(v_i)$ is defined to be the sum of distances from $v_i$ to all other vertices of $G$, i.e., the row sum $D_{i}(G)$ of $D(G)$ indexed by vertex $v_i$ and suppose that $D_1(G)\geq \cdots \geq D_n(G)$. The $Wiener~ index$ of $G$ denoted by $W(G)$ is given by $W(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…As µ α (G) ≤ T max (G) with equality if and only if G is transmission regular. Recently, Liu et al [13] showed that…”
Section: Bounds For the Distance α-Spectral Radiusmentioning
confidence: 99%
“…As µ α (G) ≤ T max (G) with equality if and only if G is transmission regular. Recently, Liu et al [13] showed that…”
Section: Bounds For the Distance α-Spectral Radiusmentioning
confidence: 99%
“…The matrix D L (G) = T r(G) − D(G) is called the distance Laplacian matrix of G, while the matrix D Q (G) = T r(G) + D(G) is called the distance signless Laplacian matrix of G. The spectral properties of D(G), D L (G) and D Q (G) have attracted much more attention of the researchers and a large number of papers have been published regarding their spectral properties, like spectral radius, second largest eigenvalue, smallest eigenvalue etc. For some recent works we refer to [3,8,4,15,17,18,19,20,21,22,25,26,27] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Another problem worth to mention is to characterize the extremal graphs for the spectral radius of a graph matrix, in some classes of graphs. For some recent works we refer to [15,19,20,22,25,26,27] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In [3], Liu, Shu and Xue studied the bounds of D max (G) − λ 1 (G) for connected nontransmission-regular graphs, and posed the following conjecture.…”
Section: Introductionmentioning
confidence: 99%